2010 5th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2010
DOI: 10.1109/hri.2010.5453272
|View full text |Cite
|
Sign up to set email alerts
|

MeBot: A robotic platform for socially embodied telepresence

Abstract: Telepresence refers to a set of technologies that allow users to feel present at a distant location, telerobotics is a subfield of telepresence. Much work has been done in telerobotics through the years to provide safer working environments for people or to reach locations that would otherwise be inaccessible. More recently telerobots have been developed for communication purposes but as of yet they have not accommodated for other channels of communication than audio or video. The design and evaluation of a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 17 publications
1
112
0
Order By: Relevance
“…Second, compared with distributed teams or remote partners, colocated teams have less trouble developing trust, coordinating work, resolving conflict, and engendering high motivation (Hinds and Bailey, 2003). Third, it was also reported that social telepresence was enhanced when the remote person's movement was augmented by a display's physical movement (Adalgeirsson and Breazeal, 2010;Nakanishi et al, 2011;Sirkin, 2012). Finally, in robot-mediated communication, the depth from motion parallax could increase the visibility of body motions.…”
Section: Robotmentioning
confidence: 99%
“…Second, compared with distributed teams or remote partners, colocated teams have less trouble developing trust, coordinating work, resolving conflict, and engendering high motivation (Hinds and Bailey, 2003). Third, it was also reported that social telepresence was enhanced when the remote person's movement was augmented by a display's physical movement (Adalgeirsson and Breazeal, 2010;Nakanishi et al, 2011;Sirkin, 2012). Finally, in robot-mediated communication, the depth from motion parallax could increase the visibility of body motions.…”
Section: Robotmentioning
confidence: 99%
“…A related question is the extent to which the media difference will involvement. Recent studies suggest that socially expressive media can significantly and it can be seen to be more engaging and likable than a static one (Adalgeirsson & Breazeal, 2010;Mutlu, Yamaoka, Kanda, Ishiguro, & Hagita, 2009). It is conceivable that the media could have some observable influence on cognitive activity such as interaction involvement.…”
Section: Conversational Involvementmentioning
confidence: 99%
“…Previous work on robot avatars has largely focused on their efficacy for interaction (e.g., [5], [13], [4]). However, there are two studies that look directly at personality perception of tele-operators.…”
Section: B Tele-operationmentioning
confidence: 99%
“…to engagement of conversational partners [4], social presence [5], group interaction [4], and trust [6].…”
Section: Introductionmentioning
confidence: 99%